Образ Сапфо в модерністському дискурсі - Турган, Ольга Дмитрівна; Turhan, O. (My University, 2021)
The article deals with the modernist reception of the literary image of the ancient poet Sappho in the works of Ukrainian writers from the end of the 19th century and beginning of the 20th – Lesya Ukrainka, M. Chernyavsky, L. Starytska-Chernyakhivska. In the main, the origins of the use of this image in the literature of different cultural epochs are clarified, and the specific nature of its interpretation in the works of different genres of these Ukrainian artists is analyzed. What is emphasized here is the originality in how Sappho’s image is interpretated and mythologized in the poems by Lesya Ukrainka and M. Chernyavsky, in L. Starytska-Chernyakhivska’s drama and in Lesya Ukrainka’s unfinished drama under the same title. The author also shows how the traditional image in these works combines both the general cultural paradigm and elements of modernist reception, and how in Ukraine this was a synthesis of Western European art canons and national specificities, of the “philosophy of life” and the “philosophy of the heart”, and of Apollonian and Dionysian elements. The author also confirms how in the works of Ukrainian writers from this period, the decisive factor in interpreting Sappho’s image is the focus on the artistic work of this ancient poet and the myth of love between Sappho and Phaon. Attention is drawn to the fact that in Lesya Ukrainka, M. Chernyavsky and L. Starytska-Chernyakhivska’s creative rethinking of this image, there is a tendency towards neomythologism, typical for modernist discourse in all kinds of art and in literature, in particular
Obraz Safony w dyskursie modernistycznym
The image of Sappho in modernist discourse
Keywords: українська література; образ Сапфо; канон; модернізм; міфологізація; Sappho; canon; modernism; mythologization; Apollonian and Dionysian elements; Safona; kanon; modernizm; mitologizacja; nurt apolliński i dionizyjski